2009
DOI: 10.1103/physrevlett.102.127003
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Doping Dependence of the Electronic Structure and Coexistence of Spin-Density-Wave and Superconductor Phases in Single CrystallineSr1xKxFe2As2

Abstract: The nature of the spin-density wave (SDW) and its relation with superconductivity are crucial issues in the newly discovered iron-pnictide superconductors. Particularly, it is unclear whether the superconducting phase and SDW are truly exclusive from each other. We here report splittings of the band structures in Sr1-xKxFe2As2 (x=0, 0.1, 0.18), and their unusual doping dependence. Our data on single crystalline samples prove that the SDW and superconductivity could coexist in iron pnictides.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 22 publications
5
38
0
Order By: Relevance
“…Below we present results for ∆ = 50 meV, which is in rough agreement with the estimates of AFM band splitting from ARPES data [33,34] and neutron scattering [35] (varying in the interval 50-100 meV), correlation length of AFM fluctuations ξ = 10a (a -lattice spacing), also in rough agrrement with netron scattering data [23,24]. In the following, all momenta are given in units of inverse lattice spacing, energies in eV.…”
supporting
confidence: 69%
“…Below we present results for ∆ = 50 meV, which is in rough agreement with the estimates of AFM band splitting from ARPES data [33,34] and neutron scattering [35] (varying in the interval 50-100 meV), correlation length of AFM fluctuations ξ = 10a (a -lattice spacing), also in rough agrrement with netron scattering data [23,24]. In the following, all momenta are given in units of inverse lattice spacing, energies in eV.…”
supporting
confidence: 69%
“…Moreover, no energy gap related to Fermi surface nesting was observed, similar to the case of the 122, 111, and 11 series. [16][17][18][19]24,33 …”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…As a result, the nature of the SDW state is exposed by the bulk band reconstruction at low temperatures. Similar to BaFe 2 As 2 and other members in the so called 122 series, [16][17][18][19] no energy gap related to nesting is observed at the Fermi surfaces of LaFeAsO. Instead, a band at high binding energies shifts down as much as 25 meV, starting from the structural transition temperature and going through the SDW transition smoothly.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The insulating parental phase even exhibits certain Mott-insulator signatures, and it is phase separated from the superconducting phase in the K x Fe 2−y Se 2 superconductor at a mesoscopic scale [7,10]. Moreover, angle-resolved photoemission spectroscopy (ARPES) studies have shown that its Fermi surface is consisted of electron pockets only [7,11,12], which is again distinct from most of the iron-based superconductors [13][14][15][16][17]. These unique properties of K x Fe 2−y Se 2 have raised a lot of interest.…”
mentioning
confidence: 99%